Amphiphilic chitosan oligosaccharide as well as preparation method and application thereof

By reacting citral with chitinoligosaccharide to form amphiphilic chitinoligosaccharides, the problem of water solubility of chitinoligosaccharides limiting their application is solved, and the preparation of various dosage forms of skin care products is achieved, and the aroma and functional effect of the product is improved.

CN119874962AActive Publication Date: 2025-04-25QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510360893.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
2045-03-26

AI Technical Summary

Technical Problem

The application of existing chitooligosaccharides in more dosage forms of skin care products is limited by their good water solubility, making it difficult to prepare multiple dosage forms.

Method used

By reacting citral with chitinoligosaccharides, amphiphilic chitinoligosaccharides are formed, which have amphiphilic and aldehyde properties, and can prepare various dosage forms of skin care products and impart them with fragrance and antibacterial and antioxidant functions.

Benefits of technology

It has realized the application of amphiphilic chitooligosaccharides in various dosage form skin care products, enhances the aroma and function of the product, and improves the moisturizing, antibacterial and antioxidant effects of the skin.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119874962A_ABST
    Figure CN119874962A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of chitosan oligosaccharide modification, and particularly relates to amphiphilic chitosan oligosaccharide as well as a preparation method and application thereof, and the structural formula of the amphiphilic chitosan oligosaccharide is as shown in a formula I: # imgabs0 # formula I; wherein m and n are positive integers, and the sum of m and n is 3-30; -N = R is a Schiff base structure formed by reaction of amino and aldehyde, and the aldehyde is citral. The aldehyde is grafted to the chitosan oligosaccharide, so that the chitosan oligosaccharide has amphipathy and aldehyde properties at the same time, skin care products of various dosage forms can be prepared by utilizing the amphipathy of the chitosan oligosaccharide, and meanwhile, the skin care products are endowed with aldehyde fragrance and effects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chitosan oligosaccharide modification, and specifically relates to amphiphilic chitosan oligosaccharide and a preparation method and application thereof. Background Art

[0002] The statements herein merely provide background information related to the present invention and do not necessarily constitute prior art.

[0003] Skin is the largest organ in the human body and undertakes vital physiological functions. From a physiological perspective, it plays a barrier function to resist the invasion of external physical, chemical and microorganisms; at the same time, it regulates body temperature, prevents excessive water loss, and maintains the stability of the body's internal environment. From a psychological perspective, healthy, smooth and elastic skin can greatly enhance a person's self-confidence and image, and make people show a more positive mental outlook in social and daily life.

[0004] As we age, our skin will inevitably develop a series of problems. In terms of appearance, the synthesis of collagen and elastic fibers in the skin decreases and degradation increases, resulting in decreased skin elasticity and wrinkles that begin to appear and deepen; subcutaneous fat is lost or its distribution changes, causing the skin to become loose; the skin's ability to retain moisture weakens, leading to dry skin problems such as rough skin and desquamation. In addition, the skin's immune function gradually declines, and its sensitivity to external stimuli increases, making it more prone to symptoms such as allergies and inflammation. These skin problems can seriously affect a person's self-confidence and quality of life.

[0005] In order to overcome the negative effects of skin aging on people, researchers continue to develop skin care ingredients with special effects. Chitosan oligosaccharides are degradation products of chitosan. They have better water solubility, antibacterial properties, antioxidant properties, biocompatibility and the advantage of promoting the growth of skin fibroblasts than chitosan. When used in skin care products, they can give skin care products moisturizing, antibacterial and anti-inflammatory properties, and slow down skin aging. However, good water solubility limits the application of chitosan oligosaccharides in more dosage forms of skin care products. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide an amphiphilic chitosan oligosaccharide and a preparation method and application thereof.

[0007] In order to achieve the above object, the present invention is implemented through the following technical solutions: In the first aspect, the present invention provides an amphiphilic chitosan oligosaccharide, the structural formula of which is shown in Formula I:

[0008] Formula I; Wherein, m and n are both positive integers, and m+n is between 3 and 30; -N=R is a Schiff base structure formed by the reaction of an amino group and an aldehyde, and the aldehyde is citral.

[0009] Citral, also known as geranial, has a strong lemon scent that can add a fresh and pleasant aroma to skin care products and enhance the sensory experience of the product; it also gives skin care products antibacterial, antioxidant, soothing and anti-inflammatory functions.

[0010] By grafting aldehyde onto chitosan oligosaccharide, chitosan oligosaccharide has both amphiphilic and aldehyde properties. Its amphiphilicity can be used to prepare skin care products of various dosage forms, and at the same time, the skin care products are endowed with the fragrance and efficacy of aldehyde.

[0011] In some embodiments, the citral is trans-citral and / or cis-citral.

[0012] Preferably, in the amphiphilic chitosan oligosaccharide, the content of trans-citral is greater than 50%. Trans-citral has a lemon fragrance, while cis-citral has no fragrance. The content of trans-citral is greater than 50% to highlight its fragrance.

[0013] In some embodiments, the molecular weight of the amphiphilic chitosan oligosaccharide before modification is less than 5000, and the degree of deacetylation is greater than 80%.

[0014] In some embodiments, the degree of substitution of the amphiphilic chitosan oligosaccharide is 10%-80%, preferably 20%-60%.

[0015] Preferably, the aggregate particle size of the amphiphilic chitosan oligosaccharide is 200-700 nm.

[0016] The aggregate particle size here refers to the particle size after standing for 21 days, and the aggregate particle size before 21 days is unstable.

[0017] Amphiphilic chitosan oligosaccharide has self-aggregation behavior, and the particle size of the aggregate is affected by the degree of substitution, the length of the hydrophobic chain and the standing time; when the chain length is equal, the greater the degree of substitution, the smaller the aggregate particle size; when the degree of substitution is equal, the longer the chain length, the larger the aggregate particle size; the amphiphilic chitosan oligosaccharide solution is left standing for 0-21 days, and as the standing time increases, the particle size gradually decreases. After 21 days, the particle size no longer changes with time. The smaller the particle size of amphiphilic chitosan oligosaccharide, the more conducive it is to penetrate the skin, so as to give full play to its advantages.

[0018] In a second aspect, the present invention provides a method for preparing the amphiphilic chitosan oligosaccharide, comprising the following steps: preparing a chitosan oligosaccharide aqueous solution and an aldehyde ethanol solution, and heating them to 30-60° C.; The ethanol solution of aldehyde is gradually added to the chitosan oligosaccharide aqueous solution, and stirring is continued during the addition process. After the addition is completed, stirring is continued for a set time to allow sufficient reaction; After the reaction is completed, the reaction system is cooled, and ethanol is removed by rotary evaporation to obtain a modified product; After freeze-drying the modified product, sponge-like amphiphilic chitosan oligosaccharide is obtained.

[0019] In some embodiments, the reaction time is 1-6 hours.

[0020] In some embodiments, the molar ratio of the aldehyde group of the aldehyde to the primary amino group in the chitosan oligosaccharide is 0.01-1:1, preferably 0.1-1:1.

[0021] In some embodiments, the freeze-drying temperature is -60 to -85°C, preferably -70 to -80°C.

[0022] In some embodiments, the vacuum degree of freeze-drying is in the range of 5-10Pa, preferably 5-10Pa.

[0023] In a third aspect, the present invention provides a method for preparing the amphiphilic chitosan oligosaccharide, comprising the following steps: mixing and grinding the aldehyde group of the aldehyde and the primary amino group of the chitosan oligosaccharide in a molar ratio of 0.01-1:1, applying a force of 5-20N during grinding, and a grinding time of 2-15min, and freeze-drying the modified product at -85°C to obtain the amphiphilic chitosan oligosaccharide.

[0024] The preparation method is a solid phase method. By changing the type of aldehyde, the molar ratio of aldehyde to chitosan oligosaccharide (measured in -NH2), the grinding force and the grinding time, amphiphilic chitosan oligosaccharide with a substitution degree between 20% and 80% can be obtained.

[0025] The liquid phase method is relatively cumbersome and time-consuming to prepare amphiphilic chitosan oligosaccharides, and waste liquid is generated during the preparation process. The solid phase method only requires pre-drying of the sample, which is simple and fast to operate, and no waste liquid is generated. If it is put into industrial production, it has obvious advantages over the liquid phase method.

[0026] During the preparation of amphiphilic chitosan oligosaccharides, if a small amount of aldehyde is not completely reacted and separated, it will remain in the amphiphilic chitosan oligosaccharide as a fragrance.

[0027] In a fourth aspect, the present invention provides the use of the amphiphilic chitosan oligosaccharide in the preparation of skin care cosmetics.

[0028] In some embodiments, the skin care cosmetics include but are not limited to lotion, moisturizer, facial mask, toner, lipstick, sunscreen, powder, makeup remover, cleanser, shower gel or shampoo.

[0029] The beneficial effects achieved by one or more embodiments of the present invention are as follows: The amphiphilic chitosan oligosaccharide provided by the present invention has the characteristics of simple preparation process, excellent performance, high safety, etc. The modified amphiphilic chitosan oligosaccharide of the present invention has the characteristics of self-aggregation in aqueous solution, and the particle size of the aggregate can be adjusted by the degree of substitution and the length of the hydrophobic segment to have good transdermal absorption performance. The modified amphiphilic chitosan oligosaccharide is non-toxic to fibroblast HFF-1, has antibacterial properties (Staphylococcus aureus, Escherichia coli, Propionibacterium acnes), has a significant inhibitory effect on the activity of inflammatory factors (TNF-2 and IL-6) and hyaluronidase, promotes fibroblast growth, has antioxidant properties (DPPH, hydroxyl free radicals, superoxide free radicals), promotes transdermal absorption, encapsulates / slowly releases oil-soluble active substances, and the self-polymer of the amphiphilic chitosan oligosaccharide also has the properties of stabilizing Pickering emulsions, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0031] Figure 1 is the infrared spectrum of the amphiphilic chitosan oligosaccharide prepared in Example 1; Figure 2 is the NMR spectrum of the amphiphilic chitosan oligosaccharide prepared in Example 1, wherein the embedded figure is a schematic diagram of the molecular structure of the amphiphilic chitosan oligosaccharide; Figure 3 3 are the thermogravimetric curves of amphiphilic chitosan oligosaccharides with different degrees of substitution prepared in Examples 1, 2 and 4; Figure 4 is the aggregate particle size distribution diagram of the amphiphilic chitosan oligosaccharide with a substitution degree of 19.9% ​​prepared in Example 2; Figure 5 is the aggregate particle size distribution diagram of the amphiphilic chitosan oligosaccharide with a substitution degree of 24.3% prepared in Example 3; Figure 6 is the aggregate particle size distribution diagram of the amphiphilic chitosan oligosaccharide with a substitution degree of 31.4% prepared in Example 1; Figure 7 is a particle size distribution diagram of the aggregates of amphiphilic chitosan oligosaccharides with substitution degrees of 19.9%, 24.3% and 31.4% prepared in Examples 1-3 after standing for 21 days; Figure 8 is a transmission electron microscopy image of the aggregate of the amphiphilic chitosan oligosaccharide with a substitution degree of 38.0% prepared in Example 5 after being left to stand for 21 days; Fig. 9The figure is a comparison of the cytotoxicity of different concentrations of amphiphilic chitosan oligosaccharides with substitution degrees of 19.9%, 24.3% and 31.4% prepared in Examples 1-3 to fibroblast HFF-1, wherein (0) is a chitosan oligosaccharide system with a concentration of 0.05 g / L; 1-a is an amphiphilic chitosan oligosaccharide with a substitution degree of 19.9% ​​and a concentration of 0.05 g / L; 1-b is an amphiphilic chitosan oligosaccharide with a substitution degree of 19.9% ​​and a concentration of 0.1 g / L; 1-c is an amphiphilic chitosan oligosaccharide with a substitution degree of 19.9% ​​and a concentration of 0.2 g / L; 2-a is an amphiphilic chitosan oligosaccharide with a substitution degree of 24.3% and a concentration of 0.05 g / L; 2-b is an amphiphilic chitosan oligosaccharide with a substitution degree of 24.3% and a concentration of 0.1 g / L; 2-c is an amphiphilic chitosan oligosaccharide with a substitution degree of 24.3% and a concentration of 0.2 g / L; 3-a is an amphiphilic chitosan oligosaccharide with a substitution degree of 31.4% and a concentration of 0.05 g / L; 3-b is an amphiphilic chitosan oligosaccharide with a substitution degree of 31.4% and a concentration of 0.1 g / L; 3-c is an amphiphilic chitosan oligosaccharide with a substitution degree of 31.4% and a concentration of 0.2 g / L; Fig.10 This is a comparison chart of the antibacterial effects of amphiphilic chitosan oligosaccharides with different degrees of substitution prepared in Examples 1-3 on Escherichia coli A, Staphylococcus aureus B and Propionibacterium acnes C, wherein A1, B1 and C1 are amphiphilic chitosan oligosaccharides with a degree of substitution of 19.9%; A2, B2 and C2 are amphiphilic chitosan oligosaccharides with a degree of substitution of 24.3%; A3, B3 and C3 are amphiphilic chitosan oligosaccharides with a degree of substitution of 31.4%; Fig.11 This is a comparative diagram of the inhibition of TNF-α and IL-6 inflammatory factors by amphiphilic chitosan oligosaccharides of different concentrations in Example 1, wherein A is TNF-α; B is IL-6; Fig.12 This is a graph showing the growth promoting effect of the amphiphilic chitosan oligosaccharide (100 μg / mL) prepared in Example 1 on fibroblasts, wherein A is the image after 0 h, B is the image after 24 h, and C is the image after 36 h (the color of the image is to distinguish the time); Fig.13 This is a graph showing the inhibitory effect of the amphiphilic chitosan oligosaccharide with a substitution degree of 31.4% prepared in Example 1 on hyaluronidase; Fig.14 : This is a comparison diagram of the transdermal absorption of chitosan oligosaccharide and the amphipathic chitosan oligosaccharide prepared in Example 1, wherein A is chitosan oligosaccharide, B is amphipathic chitosan oligosaccharide, the degree of substitution is 31.4%, (the skin used in the experiment is the abdominal skin of 5-week-old mice, in vivo experiment), and the scale is 100 μm; Fig.15The diagram is a picture showing the effect of the amphiphilic chitosan oligosaccharide self-aggregate stabilizing the Pickering emulsion prepared in Example 1, wherein A is a water phase fluorescence confocal microscopy picture, B is an oil phase fluorescence confocal microscopy picture, C is an oil-water coexistence fluorescence microscopy picture, and D is a polarizing microscopy picture, and the scale bars are all 10 μm; Fig.16 This is a Pickering emulsion diagram stabilized by amphiphilic chitosan oligosaccharide with a substitution degree of 31.4%, where a The oil content is 20%, b Oil content 30%, c Oil content 40%, d Oil content 50%, e Oil content 60%; Fig.17 The relationship between the particle size of the Pickering emulsion stabilized by amphiphilic chitosan oligosaccharide with a substitution degree of 31.4% and time; Fig.18 A comparison of the sustained release of resveratrol from Pickering emulsions stabilized by different amphiphilic chitosan oligosaccharides; Fig.19 The antioxidant effect diagram of the Pickering emulsion loaded with resveratrol stabilized by amphiphilic chitosan oligosaccharide, where (A) is the antioxidant rate against DPPH, (B) is the antioxidant rate against hydroxyl radicals, and (C) is the antioxidant rate against superoxide radicals; Fig. 20 A comparison of the photostability of resveratrol-loaded Pickering emulsions stabilized by different amphiphilic chitosan oligosaccharides. DETAILED DESCRIPTION

[0032] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0033] The following is an example of preparing amphiphilic chitosan oligosaccharide by modifying chitosan oligosaccharide with citral, and the present invention is further described in conjunction with the examples.

[0034] Example 1 The molar ratio of the aldehyde group of citral to the primary amino group -NH2 in chitosan oligosaccharide is 1:1. The corresponding masses of citral and chitosan oligosaccharide are weighed respectively. The reaction temperature is 60°C and the reaction time is 5h to obtain citral-modified amphiphilic chitosan oligosaccharide with a degree of substitution of 31.4%.

[0035] The specific steps are as follows: First, prepare a chitosan oligosaccharide aqueous solution with a concentration of 20 mg / mL and heat it to 60°C; In another beaker, prepare a 20 mg / mL ethanol solution of citral and heat the prepared solution to 60°C; The ethanol solution of citral was added dropwise to the chitosan oligosaccharide aqueous solution while stirring continuously at a speed of 300 rpm. After the addition was completed, stirring was continued at the same temperature for 5 h to allow the reaction to proceed fully.

[0036] After the reaction was completed, the reaction system was cooled to room temperature, and ethanol was removed by reduced pressure distillation using a rotary evaporator to obtain a modified product.

[0037] The modified product was freeze-dried at -85°C and 5Pa vacuum to obtain spongy citral-modified amphiphilic chitosan oligosaccharide.

[0038] Example 2 The molar ratio of the aldehyde group of citral to the primary amino group -NH2 in chitosan oligosaccharide was 1:5, the reaction temperature was 40°C, the reaction time was 2h, and citral-modified amphiphilic chitosan oligosaccharide with a substitution degree of 19.9% ​​was obtained.

[0039] The specific steps are the same as those in Example 1.

[0040] Example 3 The molar ratio of the aldehyde group of citral to the primary amino group -NH2 in chitosan oligosaccharide was 1:2, the reaction temperature was 50°C, the reaction time was 4h, and citral-modified amphiphilic chitosan oligosaccharide with a substitution degree of 24.3% was obtained.

[0041] The specific steps are the same as those in Example 1.

[0042] Example 4 The molar ratio of the aldehyde group of citral to the primary amino group -NH2 in chitosan oligosaccharide was 1:1, the reaction temperature was 50°C, the reaction time was 6h, and citral-modified amphiphilic chitosan oligosaccharide with a substitution degree of 40.0% was obtained.

[0043] The specific steps are the same as those in Example 1.

[0044] Example 5 At 25°C, the molar ratio of the aldehyde group of citral to the primary amino group -NH2 in chitosan oligosaccharide was 1:1. The mixture of citral and chitosan oligosaccharide was uniformly ground with a force of 5N for 10 minutes to obtain citral-modified amphiphilic chitosan oligosaccharide with a degree of substitution of 38.0%.

[0045] The specific steps are as follows: according to the molar ratio of the aldehyde group of citral to the -NH2 of chitosan oligosaccharide being 1:1, dry chitosan oligosaccharide is weighed and placed in a mortar, citral is added dropwise into the mortar, and at the same time, it is ground with a force of 5N. After all the citral is added, the same force is continued to be used for 10 minutes. The product is freeze-dried at -85°C and a vacuum degree of 10Pa to obtain amphiphilic chitosan oligosaccharide.

[0046] The performance test of the amphiphilic chitosan oligosaccharide prepared in the embodiment is carried out: Infrared spectrum test: Test method: Weigh about 5 mg of amphiphilic chitosan oligosaccharide, grind and mix it with dry potassium bromide, press the mixture into transparent sheets, and measure it at room temperature using a Nicolet iS10 infrared spectrometer (Tensor27, Shimadzu, Japan) with a wave number range of 4000 cm -1 -400cm -1 .

[0047] Infrared spectrum Figure 1 As shown in the figure, compared with the infrared spectrum curve of chitosan oligosaccharide, the spectrum curve of amphiphilic chitosan oligosaccharide has a peak at 1625 cm -1 、1515cm -1 and 1381cm -1 There are new peaks, which belong to the C=C double bond, C=N and C=C conjugated double bonds, and CH vibration absorption peaks on the terminal methyl group in the citral molecule; at the same time, the infrared spectrum of chitosan oligosaccharide is located at 1257cm -1 The peak intensity of is significantly weakened, which is because the N atom in the chitosan oligosaccharide molecule is linked to the hydrophobic chain segment of citral, increasing the energy required for the vibration of the CN bond. The above peak changes prove that citral is successfully connected to the chitosan oligosaccharide molecule.

[0048] MRI test: Test method: About 2 mg of amphiphilic chitosan oligosaccharide was weighed, dissolved in 1 mL of deionized water, and transferred to an NMR tube. The samples were tested in a Bruker Advance II 400 spectrometer (Bruker, Switzerland) at room temperature.

[0049] NMR spectra Figure 2 As shown, new peaks appeared at 1.21ppm, 1.44ppm, 1.33ppm, 2.03ppm and 2.19ppm. These peaks came from H on the carbon chain of citral, proving that citral was successfully attached to the chitosan oligosaccharide molecule.

[0050] Calculate the degree of substitution based on the peak area of ​​the nuclear magnetic resonance spectrum: Use the software that comes with the nuclear magnetic resonance spectrometer to integrate the characteristic peaks, and then substitute the integrated area into the calculation formula below to obtain the degree of substitution.

[0051] Taking the amphiphilic chitosan oligosaccharide prepared by citral modification as an example, the calculation formula of the degree of substitution DS is as follows: ; Among them, CH3 is Figure 2 The two -CH3 H, H b-f,f’ It is the H linked to the corresponding C on the sugar ring.

[0052] Thermodynamic stability test: About 6 mg of sample was weighed and placed in a crucible. The thermodynamic stability of the sample in the temperature range of 25-500 °C was measured using a synchronous thermal analyzer (SDT Q600, TA Instruments, USA). During the test, the heating rate was 5 °C / min and the N2 flow rate was 100 mL / min.

[0053] like Figure 3 As shown, the thermogravimetric curves of the three amphiphilic chitosan oligosaccharides with different substitution degrees prepared in Examples 1-3 are almost identical to that of chitosan oligosaccharides, proving that the thermodynamic stability of amphiphilic chitosan oligosaccharides is consistent with that of chitosan oligosaccharides.

[0054] Self-aggregation behavior (critical self-aggregation concentration): A series of amphiphilic chitosan oligosaccharide solutions with different concentrations were prepared at 25°C. Acetone was used as the solvent to prepare solutions with a concentration of 1×10 -3 Take another test tube with the same number of amphiphilic chitosan oligosaccharide solutions, add 1 mL of pyrene solution to each test tube, and then blow dry with nitrogen to keep the pyrene molecules on the inner wall of the test tube.

[0055] The prepared amphiphilic chitosan oligosaccharide solutions of different concentrations were poured into the test tubes containing pyrene to make the final concentration of pyrene 10. -5 The test tube was placed in an ultrasonic chamber at room temperature and 30 W power for 30 minutes to dissolve the pyrene molecules in the hydrophobic core of the self-aggregate, and then allowed to stand for 60 minutes.

[0056] The fluorescence changes of amphiphilic chitosan oligosaccharide solutions of different concentrations were measured on a fluorescence spectrophotometer (Hitachi F4600, Japan), and the peak intensities of the five emission peaks (373nm, 379nm, 383nm, 390nm and 397nm) were recorded. The peak intensity ratio at 373nm and 383nm was used as the ordinate (the peak intensities were recorded as I1 and I3, respectively), and the concentration of amphiphilic chitosan oligosaccharide was used as the abscissa to plot the graph. As the concentration of amphiphilic chitosan oligosaccharide increased, the position where the ratio of the two peak intensities dropped rapidly was the critical self-aggregation concentration.

[0057] Particle size and potential of self-aggregates: A certain concentration of amphiphilic chitosan oligosaccharide solution was prepared to make the solution concentration greater than the critical aggregation concentration, and the particle size and distribution of the aggregates were measured on a Zetasizer Nano ZS90 particle size analyzer (Malvern, England). At the same time, the potential value of the aggregates was obtained.

[0058] Transmission electron microscopy: The prepared amphiphilic chitosan oligosaccharide solution was dripped onto a copper grid, the aggregates were stained with phosphotungstic acid, and then the copper grid was dried. The morphology of the self-aggregates was observed under a transmission electron microscope (TEM, Tecnai-12, Philip Apparatus Co, Netherlands).

[0059] Figure 4 This is a particle size distribution diagram of the amphiphilic chitosan oligosaccharide with a substitution degree of 19.9% ​​prepared in Example 2; it can be seen from the figure that in the newly configured solution, the particle size of the aggregate is closely related to the concentration of the amphiphilic chitosan oligosaccharide, and the higher the concentration, the larger the particle size; as the standing time increases, the effect of concentration on the particle size gradually weakens. At 21 days, the particle size of the amphiphilic chitosan oligosaccharide aggregates at three concentrations is significantly smaller than the initial particle size, proving that the aggregate particle size is closely related to the standing time; Figure 5 is the aggregate particle size distribution diagram of the amphiphilic chitosan oligosaccharide with a substitution degree of 24.3% prepared in Example 3; Figure 4 Same conclusion; Figure 6 is the aggregate particle size distribution diagram of the amphiphilic chitosan oligosaccharide with a substitution degree of 31.4% prepared in Example 1; Figure 4 Same conclusion; Figure 7 The particle size distribution diagram of the aggregates of amphiphilic chitosan oligosaccharides prepared in Examples 1-3 with substitution degrees of 31.4%, 19.9% ​​and 24.3% respectively after standing for 21 days; it can be seen that the greater the substitution degree, the larger the aggregate particle size of the stable system; Figure 8 This is a transmission electron micrograph of the aggregates of the amphiphilic chitosan oligosaccharide with a substitution degree of 38.0% prepared in Example 5 after standing for 21 days; closely adjacent amphiphilic chitosan oligosaccharide aggregates can be seen, proving the formation of self-aggregates.

[0060] Antibacterial activity: tested by agar inhibition zone diffusion method.

[0061] Staphylococcus aureus, Escherichia coli and Propionibacterium acnes were used as bacterial models to test the antibacterial properties of amphiphilic chitosan oligosaccharides. The experimental process was completed in a clean bench without other bacteria. The components of the bacterial culture solution were peptone (1.0%, w / v), yeast powder (0.5%, w / v), and sodium chloride (1.0%, w / v). Agar powder (1.5%, w / v) was added to the culture solution to obtain a solid culture medium. After the configuration was completed, it was sterilized in a high-temperature and high-pressure autoclave.

[0062] Add the strain to the culture medium at a volume ratio of 1:100 into the test tube and place it in a shaker at 37°C for 12 hours. Take 80mL of the culture medium into a cell culture dish, wait for it to solidify, then smear 100μL of Staphylococcus aureus, Escherichia coli and Propionibacterium acnes on its surface, place the amphiphilic chitosan oligosaccharide circular sheets with a diameter of 6mm and a degree of substitution of 19.9%, 24.3%, and 31.4% on the culture medium containing bacteria, place the culture medium in a 37°C incubator, and observe and record the size of the inhibition zone for 12 hours.

[0063] Fig.10 is a comparative diagram of the antibacterial effects of the amphiphilic chitosan oligosaccharides with different degrees of substitution prepared in Examples 1-3 on Escherichia coli (A), Staphylococcus aureus (B) and Propionibacterium acnes (C). Fig.10 It can be seen that amphiphilic chitosan oligosaccharides have strong inhibitory effects on Escherichia coli, Staphylococcus aureus and Propionibacterium acnes, indicating that they help regulate skin microbial communities; they can prevent or improve oily skin and acne-inflamed skin, protect skin health; reduce dependence on traditional chemical preservatives, reduce the potential irritation of skin care cosmetics to the skin, and meet consumers' demand for natural and mild products. This provides theoretical evidence for the use of amphiphilic chitosan oligosaccharides as core antibacterial ingredients in cleansers and acne-removing essences; and for reducing skin inflammation and being used in soothing and repairing skin care products.

[0064] In vitro cytotoxicity: The cytotoxicity of amphiphilic chitosan oligosaccharides was detected by cell viability assay kit method, using fibroblasts as a model.

[0065] About 10,000 fibroblasts were cultured in a medium containing glucose, 10% fetal bovine serum, and 1% (v / v) penicillin-streptomycin (500 U / mL), and the well plates were placed in a biochemical incubator at 37°C for 24 h; The amphiphilic chitosan oligosaccharide prepared in Examples 1-3 was added to the wells containing cells to a final concentration of 0.05 g / L, 0.1 g / L, and 0.5 g / L in each well, and the cells were placed in a 37° C. biochemical incubator and incubated for 24 h; Then, 100 μL of 5 mg / mL 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide solution was added to each well, and the well plate was incubated in a 37°C incubator for 4 h. It was then rinsed with phosphate buffer solution and 100 μL of dimethyl sulfoxide solution was added to fully dissolve for 20 min.

[0066] The absorbance of the final sample was read at 490 nm using an ELISA reader. The absorbance of the different samples was compared with the absorbance of the blank sample to determine the cytotoxicity of the amphiphilic chitosan oligosaccharide to fibroblasts.

[0067] Fig. 9 is a comparison chart of the cytotoxicity of different concentrations of amphiphilic chitosan oligosaccharides with substitution degrees of 19.9%, 24.3% and 31.4% prepared in Examples 1-3 to fibroblast HFF-1, Fig. 9 It can be seen that amphiphilic chitosan oligosaccharides have no cytotoxicity to fibroblasts HFF-1, and have a significant growth-promoting effect on fibroblasts, such as Fig.12 As shown in A and B, it is proven to be safe for skin cells and will not cause adverse reactions such as allergies and inflammation, thereby improving the safety and applicability of the product and increasing consumers' trust in the product. When used in skin care cosmetics, it helps maintain the integrity of the skin, stimulates fibroblasts to synthesize collagen and elastic fibers, increases the elasticity and toughness of the skin, makes the skin firm and smooth, and exerts an anti-aging effect. It can be used as an effective ingredient in anti-aging skin care products and sensitive skin repair products. It can also be used in medical and cosmetic post-operative repair products to accelerate skin regeneration.

[0068] Significant inhibitory effect on TNF-α and IL-6 inflammatory factors: Mouse mononuclear macrophage leukemia cells were used as the research object. The cellular inflammation model was established by stimulating the cells with lipopolysaccharide bacterial endotoxin. Different test substances and positive controls were added and cultured for 24 hours. Then the cell supernatant was collected and the inflammatory factor release of mouse mononuclear macrophage leukemia cells was analyzed by enzyme-linked immunosorbent assay kit, and the contents of proinflammatory cytokines IL-6 and TNF-α were analyzed.

[0069] Fig.11 This is a comparative chart of the inhibition of TNF-α and IL-6 inflammatory factors by amphiphilic chitosan oligosaccharides of different concentrations in Example 1, wherein A is TNF-α; B is IL-6; and the reference group is mouse mononuclear macrophages naturally grown in a system without adding lipopolysaccharide and chitosan oligosaccharide.

[0070] Depend on Fig.11 It can be seen that amphiphilic chitosan oligosaccharides have significant inhibitory effects on TNF-α and IL-6 inflammatory factors. When used in repair creams to shield damaged skin, they can soothe the skin and relieve skin inflammation caused by external stimuli such as ultraviolet rays and pollutants; when used in anti-aging essences, they can protect collagen and elastic fibers in the skin and maintain skin elasticity and toughness; when used in sunscreens or after-sun repair products, they can reduce ultraviolet-induced oxidative stress and inflammatory responses, and enhance photoaging protection and inflammation control effects.

[0071] Inhibitory effect of hyaluronidase: The inhibition rate of amphiphilic chitosan oligosaccharides on hyaluronidase was determined by the modified Elson-Morgan method.

[0072] Fig.13 is a graph showing the inhibitory effect of the amphiphilic chitosan oligosaccharide with a substitution degree of 31.4% prepared in Example 1 on hyaluronidase. Fig.13 It can be seen that the inhibitory effect of amphiphilic chitosan oligosaccharides on hyaluronidase is significantly better than that of chitosan oligosaccharides, and the inhibition rate is positively correlated with the concentration of amphiphilic chitosan oligosaccharides. Amphiphilic chitosan oligosaccharides are used in anti-aging essences, anti-allergic essences, creams and facial masks to reduce redness, swelling and itching caused by allergies. At the same time, they prolong the moisturizing and anti-wrinkle effects of the products and are suitable for sensitive skin applications. They can be used in sunscreen and after-sun repair products to form a dual protection mechanism of "antioxidation + water retention". In the field of medical beauty, they can prolong the filling effect of hyaluronic acid, reduce inflammation and edema reactions, and can also be used in postoperative repair dressings or scar care products.

[0073] It has a significant growth-promoting effect on fibroblasts: The scratch method was used to study the effect of amphiphilic chitosan oligosaccharide on fibroblast proliferation. Before the experiment, three horizontal lines were marked on the back of the 6-well plate with a marker pen. The experiment could be started when the fibroblasts multiplied to a monolayer of adherent cells. The experiment was divided into a blank control group (Ctr) culture medium, a negative control group (NC) and a sample group (Sample).

[0074] Before timing, use a 200 μL sterile pipette tip to evenly scratch the center of the cell plate perpendicular to the baseline, and rinse the scratch three times with phosphate buffer solution, then add fresh serum-free culture medium, take pictures and time, observe and take pictures every 24 hours, and measure the scratch width. Calculate the scratch healing rate according to the following formula: Scratch healing rate (%) = (L0-L 24 ) / L0×100%; Preparation of Pickering emulsion (taking amphiphilic chitosan oligosaccharide modified by citral as an example): At room temperature, 1% amphiphilic chitosan oligosaccharide aqueous solution and 1% sodium tripolyphosphate aqueous solution were mixed at a mass ratio of 9:1, and stirred at 800 rpm for 30 minutes to obtain an aqueous phase of the emulsion. By changing the concentration of amphiphilic chitosan oligosaccharide, aqueous phases with different chitosan oligosaccharide concentrations were obtained.

[0075] At room temperature, olive oil and resveratrol are fully mixed and uniformly used as the oil phase.

[0076] At room temperature, the water phase and the oil phase were mixed in a mass ratio of 1:1 and homogenized at a speed of 8000 rpm for 3 minutes to obtain a Pickering emulsion.

[0077] Appearance of Pickering emulsions: There are two main methods for observing emulsions. The first is to take a picture of the emulsion at rest to assess the static stability of the emulsion. The second is to observe the emulsion more specifically through an optical microscope to assess the size and structure of the emulsion droplets.

[0078] Pickering emulsion droplet diameter and droplet stability: The diameter of the emulsion droplets was measured by a ZetasizerNano ZS90 (Malvern, England) laser particle size analyzer. The stability of the emulsion was evaluated by storage and centrifugation. Storage stability was mainly evaluated by the change in emulsification rate and the emulsion droplet diameter.

[0079] To further evaluate the emulsion performance, the effects of environmental factors (ionic strength (sodium chloride concentration, calcium chloride concentration), temperature (-40℃, 0℃, 25℃, 50℃ storage for 24 hours) and pH value (buffer solution, pH values ​​of 4.00, 6.86, 9.18, respectively)) on the emulsion stability were studied. All samples were tested after being stored at room temperature for 24 hours.

[0080] Pickering emulsion showed good stability in the range of -40-50ºC for 24 hours.

[0081] Fig.15 The effect diagram of the amphiphilic chitosan oligosaccharide self-aggregate stabilizing the Pickering emulsion prepared in Example 1, wherein A is a water phase fluorescence confocal microscopy image, B is an oil phase fluorescence confocal microscopy image, C is an oil-water coexistence fluorescence microscopy image, and D is a polarizing microscopy image. The scale bars are all 10 μm. Fig.15 It can be seen that the outer layer of the emulsion adsorbs amphiphilic chitosan oligosaccharide self-aggregates to stabilize the emulsion, proving the formation of Pickering emulsion; the emulsion droplets are in a polydisperse state, which is conducive to the long-term release of the encapsulated active ingredients and reduces the irritation of the active ingredients to the skin. This structure of Pickering emulsion will exert a long-lasting effect.

[0082] Fig.16 This is a Pickering emulsion diagram stabilized by amphiphilic chitosan oligosaccharide with a substitution degree of 31.4%, where a The oil content is 20%, b Oil content 30%, c Oil content 40%, d Oil content 50%, e Oil content 60%. Fig.16The particle size and potential of the Pickering emulsion were measured. The particle size of the emulsion is 200-2000nm, with a positive charge of 18-50mV. These Pickering emulsions can efficiently encapsulate oil-soluble active substances or photosensitive components. These components can be encapsulated in the hydrophobic core of the amphiphilic chitosan oligosaccharide self-aggregate or dissolved in the oil phase of the Pickering emulsion; the hydrophobic core of the self-aggregate and the oil phase of the Pickering emulsion can respectively encapsulate / dissolve different oil-soluble active substances to achieve the preparation of multi-functional Pickering emulsions; the positive charge helps the emulsion to adsorb on the skin surface and distribute evenly on the skin surface; the emulsion with a particle size of less than 500nm can penetrate the skin, and the positive charge enhances the combination of droplets with the sebum layer of the hair follicles, thereby improving the efficacy of the active substances released by the emulsion inside the skin; the emulsion with a particle size greater than 500nm can exert skin care effects by regulating the microecology of the skin surface and releasing functional ingredients on the skin surface. In addition, the emulsion with a particle size of 200-2000nm has a delicate texture, which keeps the skin fresh and comfortable, and helps to enhance the quality of skin care cosmetics.

[0083] Confocal laser scanning microscopy: Olive oil was used as the oil phase and amphiphilic chitosan oligosaccharide / sodium tripolyphosphate was used as the water phase (same as above). The dyes Nile red and Nile blue were added to the two phases for dyeing. After 12 hours, the dyed oil phase and water phase were blended and emulsified to prepare Pickering emulsion. The excitation wavelength of Nile red was 488nm and that of Nile blue was 633nm. Images were taken at 64X magnification under two wavelengths by laser confocal scanning microscopy (CLSM-TCSSP8CARS (Germany)) to obtain fluorescence confocal images of the water phase, oil phase and Pickering emulsion.

[0084] Fig.17 The relationship between the particle size of the Pickering emulsion stabilized by amphiphilic chitosan oligosaccharide with a substitution degree of 31.4% and time is shown in the figure. Fig.17 It can be seen that the particle size of the emulsion is closely related to the oil-water mass ratio. The higher the oil content, the larger the particle size of the Pickering emulsion; the particle size of the stable emulsion does not change with the standing time. Amphiphilic chitosan oligosaccharide-stabilized Pickering emulsions with different oil-water ratios can be prepared as needed.

[0085] Entrapment and release of resveratrol in Pickering emulsion: First, the UV-visible absorption spectrum of resveratrol dissolved in ethanol solution was measured, and the absorbance of each concentration gradient was recorded at 306 nm to establish a standard curve for resveratrol.

[0086] Resveratrol was encapsulated in the Pickering emulsion as the active ingredient to study the encapsulation and release behavior of the emulsion. First, 0.1 g of resveratrol was dissolved in 10 mL of olive oil and stirred at 300 rpm for 1 h at 40 ° C to fully dissolve the resveratrol. The Pickering emulsion was prepared according to the above method with the resveratrol / olive oil solution as the oil phase.

[0087] 1 mL of Pickering emulsion was diluted with 10 mL of methanol and ultrasonicated for 10 min to break the Pickering emulsion and release resveratrol. The sample was filtered with a 0.2 μm filter, and the absorbance intensity of the solution was measured with a UV-visible spectrophotometer to calculate the concentration of resveratrol.

[0088] Take another 1 mL of Pickering emulsion and centrifuge at 10000 rpm for 15 min. Collect and filter the resulting supernatant to quantitatively analyze the resveratrol in the supernatant (i.e., the resveratrol that is not encapsulated in the emulsion). The encapsulation rate EE% of resveratrol is calculated by the following formula: EE%=(amount of added resveratrol-amount of unencapsulated resveratrol) / (amount of added resveratrol)×100%.

[0089] The release behavior of resveratrol in Pickering emulsion was studied using a Franz diffusion cell with an effective diffusion area of ​​0.64 cm 2 (The contact surface between the donor chamber and the receptor chamber and between the donor chamber). The receptor chamber uses an ethanol / water solution containing 5 g / L Tween 20 (the mass ratio of ethanol to water is 1:1). The receptor medium is magnetically stirred at a speed of 600 rpm, and the constant temperature water bath temperature is maintained at 37°C. Take 300μL Pickering or resveratrol control solution (water / alcohol solution (20% v / v ethanol)) and fill it into the donor chamber. Both samples contain an equal amount of resveratrol (1 mg / mL). At a certain time interval, take out 2mL of the receptor solution and immediately add 2mL of fresh medium to ensure that the liquid volume of the receptor chamber is 5mL. A lead acetate cellulose membrane with a pore size of 0.2μm is used. The collected samples are used for resveratrol quantitative identification by UV-visible absorption spectroscopy. The cumulative release of resveratrol (%) is calculated as follows: Resveratrol release rate (%) = (cumulative release amount at a certain time) / (total amount encapsulated) × 100%.

[0090] Fig.18 Comparison of the sustained release of resveratrol from Pickering emulsions stabilized by different amphiphilic chitosan oligosaccharides. Fig.18It can be seen that Pickering emulsion can encapsulate and slowly release oily active substances (such as resveratrol), which can be quickly released in the first 2 hours with a release rate of up to 27%, and continuously released for 24 hours with a maximum release rate of about 45%. Based on the characteristics of Pickering emulsion with immediate efficacy and long-term care, enhanced and daytime protection and nighttime repair anti-wrinkle, antioxidant, whitening and spot-lightening, sunscreen and repair skin care cosmetics can be designed.

[0091] Determination of free radical scavenging ability of Pickering emulsion: (1) 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) free radical scavenging ability This experiment set up a blank control group, a solvent control group and a sample group in a 96-well plate. Three replicate wells were set for each group, with a volume of 270 μL per well.

[0092] Control group: The same volume of solvent was used to replace the test substance, and 90 μL of 0.1 mmol / L 1,1-diphenyl-2-trinitrophenylhydrazine solution was added to each well.

[0093] Sample group: Take an appropriate amount of the test substance and dissolve it in 180 μL of deionized water, and add 90 μL of 0.1 mmol / L 1,1-diphenyl-2-trinitrophenylhydrazine solution to the reaction system, so that the final concentration of the test substance in the reaction system is 1 μg / mL, 5 μg / mL, 10 μg / mL, 50 μg / mL, 100 μg / mL, and 200 μg / mL, respectively.

[0094] After mixing according to the proportion, place it on a shaker to avoid light for 15 min, and measure the absorbance intensity at 520 nm with an enzyme marker. The calculation formula for the scavenging rate of 1,1-diphenyl-2-trinitrophenylhydrazine free radical is: scavenging rate = (A0-A X ) / A0×100%; A0 represents the absorbance of the control group, A x Represents the absorbance of the substance group to be tested (OD 520 ).

[0095] (2) Hydroxyl radical scavenging ability This experiment uses the salicylic acid method, in which the hydroxyl radicals produced by the Feldmann reaction react with salicylic acid. The product has a special absorption peak at 510nm. The hydroxyl radical scavenging ability of the substance to be tested is evaluated by detecting the absorbance intensity (OD value) of the substance.

[0096] The experiment was divided into blank control group, background group, and test substance groups with different concentration gradients. The concentrations of the test substances were set to 1 μg / mL, 5 μg / mL, 10 μg / mL, 50 μg / mL, 100 μg / mL, and 200 μg / mL, and the reaction system was 1.5 mL.

[0097] The calculation formula of hydroxyl radical scavenging rate is: Clearance rate = (A0-(A x -A x0 )) / A0×100%; A0 represents the absorbance of the blank control, A x Indicates the absorbance of the substance group to be tested, A x0 Indicates the absorbance of the background group of the sample to be tested (OD 510 ).

[0098] (3) Superoxide free radical scavenging ability Under weak alkaline conditions, pyrogallol is easily self-oxidized, and the intermediate product obtained is colored with a special absorption peak at 320 nm. By measuring the change in absorbance, the effect of the test substance on the self-oxidation of pyrogallol is evaluated. If the test substance has antioxidant ability, the yield of the colored intermediate product decreases, causing the absorbance of the solution to change. This principle is used to evaluate the antioxidant ability of the test substance.

[0099] Zero adjustment solution: Take 600 μL of 0.1 M Tris hydrochloride buffer (pH = 8.2) and 600 μL of deionized water and place them in a new centrifuge tube. Mix well and place in a 25°C water bath for 20 min.

[0100] Solution I: Take 600 μL of 0.1 M Tris hydrochloride buffer (pH = 8.2) solution and 580 μL of deionized water, mix them evenly, put in the sample, set up a blank control group (solvent group), and the concentrations of the test substances in the experimental groups are 1 μg / mL, 5 μg / mL, 10 μg / mL, 50 μg / mL, 100 μg / mL, and 200 μg / mL.

[0101] Solution II: 20 μL of 5mM pyrogallol solution. In a water bath, solution I and solution II were quickly mixed at 37°C for 10 minutes, and the absorbance value (OD value) of the solution at 325nm was measured. During the measurement, the first time was recorded as 0 min, and each recording interval was 1min. The results of 5 consecutive OD values ​​were recorded. The formula for free radical scavenging rate is: Clearance = ((A0-A x )) / (A0)×100%; A0 represents the absorbance of the blank control, Ax Indicates the absorbance of the substance group to be tested.

[0102] Fig.19 The antioxidant effect diagram of the Pickering emulsion loaded with resveratrol stabilized by amphiphilic chitosan oligosaccharide, where (A) is the antioxidant rate against DPPH, (B) is the antioxidant rate against hydroxyl radicals, and (C) is the antioxidant rate against superoxide radicals. Fig.19 It can be seen that compared with the single resveratrol system, the Pickering emulsions loaded with resveratrol showed better antioxidant properties; the greater the amount of amphiphilic chitosan oligosaccharide used in the Pickering emulsion, the better the antioxidant effect of the system; the scavenging effect on DPPH and hydroxyl free radicals was better than that on superoxide free radicals, and the maximum scavenging rate for DPPH and hydroxyl oxygen free radicals was 80%, which can be used for anti-aging essences, creams, lotions, eye creams, masks and other products developed for photoaging and oxidative damage.

[0103] Photostability of Pickering emulsion after encapsulation of resveratrol: The photostability of resveratrol was studied by encapsulating resveratrol with an ethanol solution of resveratrol and a Pickering emulsion stabilized by 1.5w% and 1w% amphiphilic chitosan oligosaccharide self-aggregates. The samples containing resveratrol were irradiated with a UV lamp at 365nm for 4h. 15 mL of each sample was placed in a glass circular plate (6 cm in diameter) and placed 20 cm away from the lamp. Samples were collected after irradiation for 0.5, 1, 2, 3, and 4 h, and the content of trans-resveratrol was determined by UV-visible spectrophotometry for quantitative analysis.

[0104] Fig. 20 The photostability comparison of Pickering emulsions loaded with resveratrol stabilized by different amphiphilic chitosan oligosaccharides. Fig. 20 It can be seen that Pickering emulsion has good light stability and can effectively protect resveratrol for a long time.

[0105] Fluorescence confocal scanning microscopy (CLSM) detection of skin retention: The samples were tested for retention in the abdominal skin of 5-week-old mice, and Nile red was used as a fluorescent probe to observe the retention and distribution within the skin layers. This technique has become a recognized technique for detecting the distribution of hydrophobic drugs in different skin layers. The Pickering emulsion formulation was prepared using 0.01% w / v Nile red according to the above steps. The control sample was prepared by dissolving an equal amount of Nile red in olive oil. 500 μL of Pickering emulsion (or control sample) was applied to the abdomen of the mouse. After 6 hours, the skin samples were removed and thoroughly washed with deionized water and phosphate buffer to remove any excess undiffused Nile red. The skin samples were placed in tissue freezing medium and frozen at -20°C overnight. The next day, the samples were cryosectioned using a cryostat with a section thickness of 80 μm. The sections were covered with a small amount of mounting medium and a cover glass and observed using a fluorescence confocal at an excitation wavelength of 561 nm and emission wavelengths of 570 nm and 691 nm.

[0106] Depend on Fig.14 As shown in Figures A and B, a large amount of red dye in the Pickering emulsion stabilized by amphiphilic chitosan oligosaccharide penetrates into the skin, and the red area is much larger than that of the chitosan oligosaccharide / ethanol solution system. Moreover, the red color is more evenly distributed, indicating that the Pickering emulsion stabilized by amphiphilic chitosan oligosaccharide has a stronger transdermal effect. The software provided by the fluorescence confocal scanning microscope calculates that the depth of the dye in the Pickering emulsion in the sliced ​​skin is 55 μm, which is deeper than the depth of the dye in the chitosan oligosaccharide / ethanol system penetrating into the skin, further proving that amphiphilic chitosan oligosaccharide has the ability to promote penetration.

[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An amphiphilic chitosan oligosaccharide, characterized in that: Its structural formula is shown in Formula I: Formula I; Wherein, m and n are both positive integers, and m+n is between 3 and 30; -N=R is a Schiff base structure formed by the reaction of an amino group and an aldehyde, and the aldehyde is citral.

2. The amphiphilic chitosan oligosaccharide according to claim 1, characterized in that: The citral is trans-citral and / or cis-citral, and the content of trans-citral in the amphiphilic chitosan oligosaccharide is greater than 50%.

3. The amphipathic chitosan oligosaccharide according to claim 1, characterized in that: The molecular weight of the amphiphilic chitosan oligosaccharide before modification is less than 5000, and the degree of deacetylation is greater than 80%.

4. The amphiphilic chitosan oligosaccharide according to claim 1, characterized in that: The degree of substitution of the amphiphilic chitosan oligosaccharide is 10%-80%.

5. The amphiphilic chitosan oligosaccharide according to claim 1, characterized in that: The aggregate particle size of the amphiphilic chitosan oligosaccharide is 200-700nm.

6. The method for preparing the amphiphilic chitosan oligosaccharide according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: preparing a chitosan oligosaccharide aqueous solution and an aldehyde ethanol solution, and heating the solution to 30-60° C.; Gradually add the ethanol solution of aldehyde to the chitosan oligosaccharide aqueous solution, stirring continuously during the addition process. After the addition is completed, continue stirring for 1-6 hours to allow for sufficient reaction; After the reaction is completed, the reaction system is cooled, and ethanol is removed by rotary evaporation to obtain a modified product; After freeze-drying the modified product, sponge-like amphiphilic chitosan oligosaccharide is obtained.

7. The method for preparing amphiphilic chitosan oligosaccharide according to claim 6, characterized in that: The molar ratio of the aldehyde group of the aldehyde to the primary amino group in the chitosan oligosaccharide is 0.01-1:

1.

8. The method for preparing the amphiphilic chitosan oligosaccharide according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: mixing and grinding the aldehyde group of aldehyde and the primary amino group of chitosan oligosaccharide at a molar ratio of 0.01-1:1, applying a force of 5-20N during grinding for 2-15 minutes, and freeze-drying the modified product at -85°C to obtain amphiphilic chitosan oligosaccharide.

9. Use of the amphiphilic chitosan oligosaccharide according to any one of claims 1 to 5 in the preparation of skin care cosmetics.

10. The use according to claim 9, characterized in that: The skin care cosmetics include but are not limited to lotion, moisturizer, facial mask, toner, lipstick, sunscreen, powder, makeup remover oil, cleanser, shower gel or shampoo.

Citation Information

Patent Citations

  • Citral Pickering emulsion and preparation method thereof

    CN108783373A

  • Application of vanillin crosslinked chitosan oligosaccharide mono guanidine hydrochloride in preparation of anti-oxidation drugs

    CN109575325A

  • Preparation method of pH-responsive chitosan-citral-zinc p-coumarate compound with vibrio resistance and antioxidant activity

    CN117924808A

  • Preparation method of chitosan-citral-zinc tannate particles with anti-vibrio activity

    CN118948890A